2001
DOI: 10.1590/s1519-566x2001000400020
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da Densidade de Presas e do Acasalamento na Taxa de Predação de Fêmeas de Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae) em Condições de Laboratório e Campo

Abstract: The predation rate of unmated and mated females of Podisus nigrispinus (Dallas) was evaluated on different densities of Alabama argillacea (Huebner) caterpillars (50 ± 10 mg), in laboratory and field conditions. In the laboratory, the predator females were maintained in 500 ml plastic jars with five different densities of prey (one, two, four, eight, and 16). In the field, caterpillars at the same densities were caged on flowering cotton plants. Under both conditions, females gained weight and increased the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
1
7
0
3
Order By: Relevance
“…As plantas confinadas apresentaram área foliar variando de 0,55 a 0,68 m 2 , determinada pelo modelo obtido por Oliveira et al (2001). As gaiolas foram mantidas com a parte superior aberta até a liberação das lagartas e predadores e, imediatamente, pulverizadas e fechadas.…”
Section: Toxicidade De Inseticidas E Acaricidas Ao Percevejounclassified
“…As plantas confinadas apresentaram área foliar variando de 0,55 a 0,68 m 2 , determinada pelo modelo obtido por Oliveira et al (2001). As gaiolas foram mantidas com a parte superior aberta até a liberação das lagartas e predadores e, imediatamente, pulverizadas e fechadas.…”
Section: Toxicidade De Inseticidas E Acaricidas Ao Percevejounclassified
“…Using similar data, Oliveira et al (2001) also found that, both in the laboratory and in the field, the increasing density of A. argillacea allowed P. nigripinus to locate the prey more easily.…”
Section: Predatory Capacity Of Podisus Nigripinusmentioning
confidence: 70%
“…Avaliando a taxa de predação em folhas de algodoeiro, OLIVEIRA et al (2001) parece não influenciar o teor dos elementos nas folhas (MALAVOLTA et al 1997), embora as folhas voltadas para o oeste, em geral, mostram mais intensamente sintomas de carência (de boro e zinco, principalmente). Para diminuir o erro na variação, esses autores recomendam colher as amostras nas quatro exposições (N, S, L e O) em plantas à meia-sombra.…”
Section: Resultsunclassified